Secondary prevention of cerebrovascular events in patients with "asymptomatic" atherosclerotic stenosis of the vertebral arteries and unfavorable prognostic factors of chronic cerebral ischemia. (14th October 2021) - Shugushev, Z; Karasev, S; Maximkin, D; Volkov, S; Korobkov, A; Bagin, S; Chepurnoy, A
Abstract: Aim: To evaluate the three-year results of endovascular interventions in patients with "asymptomatic" atherosclerotic stenosis of the vertebral arteries as a method of secondary prevention of cerebrovascular events. Material and methods: The patients were randomized into 2 groups: in group I (n=60), secondary prevention of cerebrovascular events were carried out in a combined strategy - stenting of the vertebral arteries in combination with medication therapy, and in group II (n=60) - only medication therapy. Long-term follow-up were planned in 12, 24 and 36 months. Inclusion criteria: patients with "asymptomatic" stenosis of the vertebral arteries 50–95%; the diameter of the vertebral arteries is not less than 3.0 and not more than 5 mm; the presence of not gross cerebral and focal symptoms corresponding to the initial (asymptomatic) stage of encephalopathy (according to E.V. Schmidt); the presence of at least one factor for an unfavorable prognosis of chronic cerebral ischemia: arrhythmia, total cholesterol level more than 6.0 mmol / l, open Willis circle, arterial hypertension, bilateral lesion of the vertebral arteries, low-density lipoprotein level more than 3.5 mmol / l, combined lesion of the vertebral and carotid arteries, calcification of the vertebral arteries, a coronary heart disease in anamnesis. Primary endpoints: the total incidence of cardiovascular events. Results: In all patients from group I, stenting of the vertebral arteries was performed without the use of embolic protection devices. The total incidence of major cerebral complications by the end of the study was 5.9% in group I and 25.0% in group II (χ 2 =4.825; p=0.023). In group I by the end of the study, the total incidence of stroke was 2.9%, and in group II it reached 30.5%. The total frequency of transient ischemic attack was 5.8 and 8.3%, respectively (χ 2 =4.135; p=0.042). The incidence of cardiac complications was 8.8 and 27.8%, respectively, in groups I and II (χ 2 =4.154; p=0.042). The survival rate, free from major cerebral complications, as well as cardiac complications, was significantly higher in patients who received combined treatment (vertebral artery stenting in combination with drug therapy). The survival rate of patients from group I, free from restenosis, was 94.12±4.03%. In general, restenosis in 6.45% of patients in the combination treatment group, however, restenosis itself did not affect the incidence of major cerebral complications in the long-term period (χ 2 =0.6911; p=0.4057). Conclusion: In patients with "assymptomatic" atherosclerotic lesions of the vertebral arteries and with factors of poor prognosis of cerebral artery diseases, secondary prevention of cerebrovascular events is advisable to carry out a combined method, including stenting of the vertebral arteries, in combination with drug therapy. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Russian academic excellence project 5-100